Use of Remote Access Technologies and WebLabs as Teaching-Learning Strategy in Engineering - Wânderson de Oliveira Assis; Alessandra Dutra Coelho (The Journal of Engineering and Exact Sciences)
This work presents the use of technological tools and remote laboratories developed in order to teaching process control in engineering courses. The proposal is to demonstrate tools that can be used to allow teaching mediated by technologies, with their benefits and limitations, considering the need to carry out practical activities to complement the theoretical classes aiming at better assimilation of the contents for an effective learning. Furthermore, an overview of projects using remote laboratories developed are presented, such as: “WebLab for Speed ??and Position Control of DC Motor”, “WebLab for Mobile Robot Motion Control”, “WebLab for Temperature Control of a Didactic Oven" and finally a "Level Control System with Remote Web Access". This last remote laboratory will be detailed showing the didactic resources used, the available functionalities, the experiments available and the first steps for those who want to implement a remote laboratory for process control.